Bank Profitability and Risk-Taking - Martynova, Natalya (IMF Working Papers; Working Paper ;, 2015)
Traditional theory suggests that more profitable banks should have lower risk-taking incentives. Then why did many profitable banks choose to invest in untested financial instruments before the crisis, realizing significant losses? We attempt to reconcile theory and evidence. In our setup, banks are endowed with a fixed core business. They take risk by levering up to engage in risky 'side activities'(such as market-based investments) alongside the core business. A more profitable core business allows a bank to borrow more and take side risks on a larger scale, offsetting lower incentives to take risk of given size. Consequently, more profitable banks may have higher risk-taking incentives. The framework is consistent with cross-sectional patterns of bank risk-taking in the run up to the recent financial crisis.